The Application of the Analytical Network Process for Select Leaders in Higher Education Institutions - Phan Hong Hai; Nguyen Anh Tuan; Vo Van Tuyen (Bright Publisher, 2026)
This study aims to examine the application of the Analytic Network Process (ANP) in selecting leaders for public universities in Vietnam. The research seeks to develop a transparent, scientific, and decision-making framework for evaluating leadership candidates based on multiple interrelated criteria in higher education governance. Empirical data were collected from experts, lecturers, and students at a public university in Vietnam, with a total sample size of 257 respondents. The research employed pairwise comparison matrices and ANP procedures, including criteria identification, consistency testing, weight calculation, and candidate ranking. Five criteria were identified for evaluating leadership candidates: professional qualifications and scientific research capacity, ethics and integrity, experience in management and organization, ability to inspire colleagues and students, and ability to mobilize financial resources. The results indicate that ethics and integrity (C2) with weight (0.2550), ability to mobilize financial resources (C5) with weight (0.2350), and experience in management and organization (C3) with weight (0.2309) were the most influential factors in leadership selection. Based on these weighted criteria, three leadership candidates were evaluated and ranked, demonstrating the suitability and effectiveness of the ANP model in supporting decisions for selecting university leaders. The study provides a scientifically based, transparent assessment tool while suggesting policy implications in senior human resource management, in line with the requirements of innovation and sustainable development of Vietnamese higher education.